THE WEBSITE-BASED MAKASSAR AVIATION POLYTECHNIC E-LEARNING APPLICATION DESIGN USES MOODLENESIA (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2023)
Desain of Aviation Polytechnic of Makassar E-Learning application website base using Moodlenesia created by Citra Astri Lestari at Bumi Permata Sudiang Block E1 No. 31, Biring Kanaya, Makassar, South Sulawesi. E-Learning is one of the technologies that serves to help teaching and learning activities. E-learning is growing rapidly. There are many platforms available to create E-Learning. One of them is Moodlenesia. Moodlenesia is a platform available on the website to create E-Learning. Moodlenesia has almost the same add-ins as Moodle, it's just that Moodlenesia is paid. This research method is based on the Government's Decision on the Implementation Learning during the Coronavirus Disease Pandemic Period 2019 (Covid-19). The instruments that we used are laptops or PCs and the internet. The results of this study show that using Moodlenesia in creating an E-Learning application is very easy. We can set its features, manage its users, and others. E-Learning by using Moodlenesia can make this current distance learning process run effectively. ABSTRAK Rancangan aplikasi E-Learning Politeknik Penerbangan Makassar berbasis website menggunakan Moodlenesia. E-Learning merupakan salah satu teknologi yang berfungsi untuk membantu kegiatan belajar mengajar. E-Learning saat ini berkembang sangat pesat. Banyak sekali platform-platform yang tersedia untuk membuat E-Learning. Salah satunya adalah Moodlenesia. Moodlenesia adalah platform yang tersedia di website untuk membuat E-Learning. Moodlenesia ini mempunyai add-ins yang hampir sama dengan Moodle, hanya saja Moodlenesia berbayar. Metode penelitian ini berdasarkan Keputusan Pemerintah tentang Penyelenggaraan Pembelajaran Di Masa Pandemi Coronavirus Disease 2019 (Covid-19). Instrumen yang digunakan pada penelitian ini adalah laptop atau PC dan internet. Hasil penelitian ini menunjukkan bahwa menggunakan Moodlenesia dalam membuat sebuah aplikasi E-Learning sangat mudah. Kita dapat mengatur fitur-fiturnya, mengatur penggunanya, dan lain-lain. E-Learning dengan menggunakan Moodlenesia ini bisa mengefektifkan proses pembelajaran jarak jauh saat ini.